Saturday

March 28, 2015

March 28, 2015

Posted by **joey** on Thursday, February 9, 2012 at 9:40pm.

- analytic geometry -
**Reiny**, Thursday, February 9, 2012 at 11:15pmlet's complete the square ...

4x^2 + 56x - (y^2 - 2y ) = -195

4(x^2 + 14x +**49**) - (y^2 - 2y +**1**) = -195 + 4(49) - 1

4(x+7)^2 - (y-1)^2 = 0

ahh, we have a degenerated hyperbola

the hyperbola has degenerated into its asymtotes

notice we have a difference of squares = 0

so

2(x+7) + (y-1) = 0 or 2(x+7) - (y-1) = 0

2x + 14 + y - 1 = 0 or 2x + 14 - y + 1 = 0

2x + y = -13 or 2x - y = -15

the "centre" would be the intersection of the two lines.

**Answer this Question**

**Related Questions**

Analytic Geometry - x^2-y^2-6x+8y-3=0 Find the center vertices, foci, and ...

(Please Help!) Analytic Geometry - Find the equation of the parabola with ...

Please Help ! Analytic Geometry - Find the equation of the parabola with ...

Math - Find the vertices, center, asymptotes, and foci of the ellipse and sketch...

analytic geometry - Find the equation of the hyperbola. Transverse axis parallel...

Analytic Geometry - What are the equations of the circles tangent to the x-axis...

Pre-calculus - For the ellipse with equation 5x^2+64y^2+30x+128y-211=0, find the...

analytic geometry/graphing problem - The vertices of a triangle are the points ...

analytic geometry - the base of an isoceles triangle lies on the x-axis. The ...

Please help on geometry - analytic geometry - What is the area, in square units...